2010
DOI: 10.3402/ijch.v69i3.17603
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in pregnancy and its association with pregnancy outcomes in the Arctic Russian town of Monchegorsk, 1973–2002

Abstract: Objectives. The purpose of this study was to determine the prevalence of anemia in pregnancy in Monchegorsk, north-west Russia, and to analyse its association with birth weight and the risk of stillbirth and preterm birth. Study design. A registry study based on the Kola Birth Registry. Methods. A total of 24,525 women who gave birth in Monchegorsk between 1973 and 2002 and who had data on anemia in pregnancy in the Kola Birth Registry (KBR) were included in the study. For these women, data on maternal anemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
2
9
0
3
Order By: Relevance
“…Observational studies published over the past decade [7][8][9] suggested the association between maternal Hb concentration and birth weight: however, findings from some studies are uncertain. [21,29,35,36] However, a recent study has suggested a U-shaped relationship between maternal Hb and birth weight, [10] with contemporary research supporting a potential association between high Hb levels and reduced birth weight. Published reviews of observational studies have certain limitations as mentioned earlier, and no detailed review is published about maternal Hb levels and birth weight.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies published over the past decade [7][8][9] suggested the association between maternal Hb concentration and birth weight: however, findings from some studies are uncertain. [21,29,35,36] However, a recent study has suggested a U-shaped relationship between maternal Hb and birth weight, [10] with contemporary research supporting a potential association between high Hb levels and reduced birth weight. Published reviews of observational studies have certain limitations as mentioned earlier, and no detailed review is published about maternal Hb levels and birth weight.…”
Section: Objectivesmentioning
confidence: 99%
“…Forty-two abstracts were deemed eligible for full-text assessment [ Figure 1]. Nine studies [42][43][44][45][46][47][48][49][50] were excluded after full-text in Asia, [7,8,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] nine in Africa, [9,[29][30][31][32][33][34][35][36] , one in Europe, [37] two in North America, [38,39] and two in South America. [40,41] Sample size ranged from 50 to 88,149.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…14 Indicadores sociais como área de residência, escolaridade e tipo de trabalho influenciaram a prevalência de anemia, assim como influencia a Segurança Alimentar e Nutricional. 15 A pobreza atinge todos os membros do domicílio e a experiência de insegurança alimentar e fome gera preocupação nas mães em relação à nutrição infantil, sentimentos de dor intensa, desamparo e desesperança em relação ao futuro 16 . Isso revela a face interdisciplinar da segurança alimentar e nutricional, pois a mesma abrange aspectos sociais, culturais, psicológicos, políticos, ambientais, nutricionais e de saúde.…”
Section: Discussionunclassified
“…Os resultados mostram que a prevalência de anemia em gestantes tem aumentado ao longo dos anos, 14,15,16,17 e varia conforme o nível de escolaridade, área de residência, tipo de trabalho da mulher, 14 ter ou não parceiro conjugal 18 e idade materna mais jovem. 19 Anemia durante a gestação mostrou influenciar condições de saúde do recém nascido, estando associado com o peso ao nascer acima 14,19,20 ou abaixo do recomendado, 14,21,22,23,24 anemia no recém-nascido, 8 natimortos 19 e restrição do crescimento intra-uterino, 23 sendo considerada fator de risco pré-natal independente para baixo peso ao nascer, assim como menos de 4 consultas e ausência de cuidados no pré-natal, parto prematuro e eclampsia.…”
Section: Métodosunclassified
See 1 more Smart Citation